Development status of rural informatization in Beijing, China - Yu, Ying; Xiangyang, Qin; Lidong, Zhang (International Journal of Agricultural and Biological Engineering, 2012)
The development status of rural informatization in Beijing was analyzed from three aspects, which include infrastructure building, resource platform and service system construction, and the information technology application in rural areas. ?The infrastructure building in Beijing had certain scale, and the network coverage in rural counties and the rate of network into villages almost reached 100%. ?The construction of resource platform and service systems was diversified and it provided various types of services for farmers